2021
DOI: 10.2169/internalmedicine.6399-20
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Eosinophilic Granulomatosis with Polyangiitis Simultaneously Demonstrating Various Clinical Manifestations with Retroperitoneal Fibrosis and Membranous Nephropathy

Abstract: The first case of eosinophilic granulomatosis with polyangiitis (EGPA) simultaneously demonstrating various clinical manifestations, including retroperitoneal fibrosis (RPF) causing hydronephrosis and membranous nephropathy (MN) leading to nephrotic syndrome, is presented. There have been no previous case reports demonstrating the simultaneous onset of these three disease categories with significant complex pathologies. This case was successfully managed by providing adequate combination therapies according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…1 However, although rare, large Vasculitis Vasculitis Vasculitis vessels involvement, including aortitis and periaortitis, has been described in AAVs, mainly in GPA and MPA, 2 3 and is usually non-stenosing, consisting of perivascular soft tissue masses, aneurysms, dissection and rupture. 3 With regard to EGPA, to our knowledge, only four cases of periaortitis have been reported in the literature, [4][5][6][7] and are summarised in table 1. The suggested underlying pathophysiology is a vasa-vasoritis of the aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, although rare, large Vasculitis Vasculitis Vasculitis vessels involvement, including aortitis and periaortitis, has been described in AAVs, mainly in GPA and MPA, 2 3 and is usually non-stenosing, consisting of perivascular soft tissue masses, aneurysms, dissection and rupture. 3 With regard to EGPA, to our knowledge, only four cases of periaortitis have been reported in the literature, [4][5][6][7] and are summarised in table 1. The suggested underlying pathophysiology is a vasa-vasoritis of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 With regard to EGPA, only four cases of periaortitis have been reported in the literature. [4][5][6][7] Dupilumab is a human monoclonal IgG 4 antibody that targets the interleukin-4 receptor subunit α of the IL-4 and the IL-13 receptors. It is used in the treatment of atopic dermatitis, uncontrolled asthma with hypereosinophilia and chronic sinusitis with nasal polyposis.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the clinicopathological features described in the six previous case reports of EGPA complicated with MN, including both ANCA-positive [4][5][6] and negative cases [7,8], with our case (Table 1). We found that those with rapidly progressing renal deficiency demonstrated NCGN histologically, except for our case, and that renal function was recovered in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently reported that 10% of EGPA was complicated with non-NCGN, such as membranous nephropathy (MN), of which most were ANCA negative [3]. Furthermore, MN complicated in EGPA has been previously reported for both ANCA-positive [4][5][6] and -negative [7,8] cases. Although ANCA is recognized as a useful marker to differentiate the heterogeneous clinical spectrum of EGPA [9], it is difficult to clarify all clinical findings from ANCA results given the aforementioned exceptions.…”
Section: Introductionmentioning
confidence: 99%